2016
DOI: 10.1088/0957-4484/27/14/145601
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals stacks of few-layer h-AlN with graphene: anab initiostudy of structural, interaction and electronic properties

Abstract: Gueorguiev, Van der Waals stacks of few-layer h-AlN with graphene: an ab initio study of structural, interaction and electronic properties, 2016, Nanotechnology, (27) Here, by employing vdW-corrected density functional theory calculations, we investigate structure, interaction energy, and electronic properties of van der Waals stacking sequences of few-layer h-AlN with graphene. We find that the presence of a substrate such as graphene induces enough interlayer charge separation in h-AlN, favoring a graphite-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…Similarly, the structure, interlayer interaction energy, and electronic properties of SL and few-layer h-AlN on graphene were also investigated within DFT. 115 It was found that dynamically stable few-layer h-AlN can form on graphene, where interlayer interaction between h-AlN layers is stronger than that between h-AlN and graphene. Also, the electron density of h-AlN layers is not significantly modified upon stacking.…”
Section: Effect Of Substratementioning
confidence: 99%
“…Similarly, the structure, interlayer interaction energy, and electronic properties of SL and few-layer h-AlN on graphene were also investigated within DFT. 115 It was found that dynamically stable few-layer h-AlN can form on graphene, where interlayer interaction between h-AlN layers is stronger than that between h-AlN and graphene. Also, the electron density of h-AlN layers is not significantly modified upon stacking.…”
Section: Effect Of Substratementioning
confidence: 99%
“…Recent ab initio investigations, motivated by the perspectives for highimpact applications such as room-temperature spintronics at the nanoscale, 3 reported on the structural, vibrational, and electronic properties of single and few-layer graphitic-like AlN, 4 including in heterostructures with graphene. 5 The MOCVD of AlN on epitaxial graphene has also been attempted. 6 MOCVD processes are regulated by a complex interplay between precursor/precursor and precursor/surface reaction thermodynamics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…This observation has been explained by density functional theory (DFT) calculations that h‐BN has an energetic advantage over WZ by eliminating the unstable dipole moment when the number of the hexagonal layers is smaller than a certain value . By the same scheme, it has been predicted that h‐BN may also be stabilized in other WZ crystals such as AlN, GaN, and SiC …”
Section: Dft Calculations For 14 Selected Ab Compounds Together Withmentioning
confidence: 99%
“…[10] By the same scheme, it has been predicted that h-BN may also be stabilized in other WZ crystals such as AlN, GaN, and SiC. [11][12][13] According to previous experimental and theoretical studies, two ways have been used to observe the h-BN structure in WZ crystals: (1) by applying an external pressure; (2) by reducing the number of the hexagonal layers in WZ crystals. In both ways, the h-BN structure is stabilized enthalpically/energetically.…”
mentioning
confidence: 99%